Pendampingan Pembuatan Data Digital Manggis pada Kelompok Tani Bina Mandiri Dusun Nyiurbaye Gawah, Lombok Barat - Kurniawan Yuniarto; Joko Sumarsono; Cahyo Mustiko Okta Muvianto; Muhamad Ihsan Febriyanto Mbele (Institut Pertanian Bogor, 2021)
A digital database of agricultural commodities is indispensable in the 4.0 and social revolution eras of 5.0. The creation of a mangosteen agricultural information system at the Bina Mandiri farmer group is vital to support the sustainability of farming activities in preparation for future export administration. This dissemination was carried out in collaboration with members of the Bina Mandiri farmer group, Nyiurbaye Gawah hamlet, Batu Mekar village, West Lombok district. The purpose of this activity is assistance in digitizing mangosteen trees in making digital maps of mangosteen distribution in the Bina Mandiri farmer group. The implementation of this activity includes: socializing the importance of digital data, collecting primary data and creating a mangosteen agriculture information system that can be connected to a WebGIS page. The result of this activity is the transfer of knowledge and technology of mangosteen mapping to the Bina Mandiri farmer group. In addition, the Bina Mandiri farmer group has digital data related to land and mangosteen trees so that it can be useful for sustainable management and utilization of the remaining space on land for planting mangosteen trees and knowledge of spacing errors that have occurred in the practice of planting mangosteen.